Diversity and Inclusion: Impacts on Psychological Wellbeing Among Lesbian, Gay, Bisexual, Transgender, and Queer Communities - Chan, Alex Siu Wing; Wu, Dan; Lo, Iris Po Yee; Ho, Jacqueline Mei Chi; Yan, Elsie (Frontiers in Psychology, 2022)
For scholars, practitioners, and legislators concerned about adolescents from sexual minority, the main goal has been creating more positive and inclusive learning environments for these individuals in the past decade. Numerous factors, such as repeated patterns of homophobic bullying by classmates and other grown-ups in school, have been a significant barrier to achieving this goal. In addition, lesbian, gay, bisexual, transgender, and queer (LGBTQ) adolescents encounter substantial inequality across a broad spectrum of wellbeing and education consequences. Compared with their heterosexual counterparts, LGBTQ adolescents experience increased anxiety, depression, suicidal thoughts, antisocial behavior, poorer academic performance, reduced school attachment and protection, and a weaker desire to finish their studies. Such discrepancies based on gender and sexuality were linked to more maltreatment encountered by LGBTQ adolescents. It is crucial to recognize the backgrounds and expectations of LGBTQ adolescents to offer them the best resources. To overcome the inequality and obstacles faced by these LGBTQ adolescents and foster their endurance, it is essential to examine tools and techniques that can be utilized. This study examined the literature that explains why society fails to provide enough support to LGBTQ students. Thus, mechanisms explaining how LGBTQ adolescents interact with others in the learning environment and how such discrepancies arise will be examined. Following that, violence and prejudice, which are fundamental causes of psychological problems among LGBTQ adolescents, will be explored.